Risiko Litigasi sebagai Variabel Pemoderasi Pengaruh Kualitas Laporan Keuangan pada Efisiensi Investasi - Ardana, I Gusti Putu Suma; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p21, 2018)
Investment are deemed to be efficient if the resources owned are used appropriately, and there’s no waste of resources. This research aims to earn an empirical evidence of the litigation risk as moderating variable in the effect of the quality of financial statements on investment efficiency. The population on this research was conducted on mining companies listed in the Indonesian Stock Exchange in the period 2013- 2015. Sample chosen by non-probability sampling method with purposive sampling technique. The samples in this research were 96 financial statements data of mining companies listed in the Indonesian Stock Exchange in period 2013-2015. The analysis technique used was ordinary linear regression and Moderated Regression Analysis (MRA). From the result, it can be concluded that quality of financial statements has positive effect on investment efficiency and litigation risk weaken the effect of the quality of financial statements on investment efficiency. Keywords : Investment efficiency, statement’s quality, litigation.